Psychological and Pedagogical Diagnostics of Learning Outcomes in Higher Education Institutions - Rebukha, Liliia; Bohush, Maksym (Pedagogical Discourse, 2025)
The increasing complexity of the educational process, including the spread of distance and blended learning formats, poses a challenge for higher education institutions to ensure objectivity and reliability in student assessment. Traditional evaluation methods often prove to be insufficiently effective or informative. Highlighting and analyzing specific aspects of psychological and pedagogical diagnostics enhances the objectivity of assessing students’ learning achievements and their adaptability to the new realities of the modern educational environment. It also helps to identify factors that contribute to the effective development of practical measures aimed at fostering students’ competence and improving the overall quality of the educational process. The article analyzes the essence, content, functions, and methods of psychological and pedagogical evaluation (using the example of psychological and pedagogical diagnostics) of learning outcomes in higher education institutions. A theoretical analysis of scientific approaches to understanding diagnostics as a component of education quality management is presented. Psychological and pedagogical diagnostics is defined as a system of analytical and prognostic activities performed by the teacher to identify, measure, and evaluate students’ levels of competence. Particular attention is paid to the principles of objectivity, consistency, humanization, and the integration of digital technologies into the assessment process. It is emphasized that in modern psychological and pedagogical practice, comprehensive mixed assessment ‒ combining traditional approaches with digital diagnostic tools ‒ plays a crucial role. The author proposes a conceptual vision for developing the diagnostic culture of higher education teachers. It is concluded that psychological and pedagogical evaluation of learning outcomes in higher education institutions is an effective means of monitoring educational achievements and serves as an essential intellectual system for managing and improving the quality of higher education.